Regional differences in the pigmentation of skin in camel - GOSWAMI, S K; DHINGRA, L D; NAGPAL, S K (The Indian Journal of Animal Sciences, 2013)
The skin of camel was moderately pigmented over general body areas. The lateral body areas, upper lip. lower lip, nostnls and upper eyelid were comparatively more pigmented than other areas studied. The melanin pigment was seen in medulla, cortex and outer root sheath of hair follicle and also in the epithchum of sweat gland duel.